2023
DOI: 10.3389/fevo.2023.1066022
|View full text |Cite
|
Sign up to set email alerts
|

Timeless or tainted? The effects of male ageing on seminal fluid

Abstract: Reproductive ageing can occur due to the deterioration of both the soma and germline. In males, it has mostly been studied with respect to age-related changes in sperm. However, the somatic component of the ejaculate, seminal fluid, is also essential for maintaining reproductive function. Whilst we know that seminal fluid proteins (SFPs) are required for male reproductive success across diverse taxa, age-related changes in SFP quantity and composition are little understood. Additionally, only few studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 145 publications
(164 reference statements)
1
11
0
Order By: Relevance
“…First, while we found that increasing the proportion of lifespan sampled by a study yielded greater evidence for senescence (also shown by Fricke et al, 2023;Vrtilek et al, 2022), studies tended to sample a low proportion of maximum adult lifespan (median = ~25%, Supplementary Fig. 10).…”
Section: Aim 1: Effects Of Advancing Male Age On Ejaculate Traitssupporting
confidence: 67%
See 4 more Smart Citations
“…First, while we found that increasing the proportion of lifespan sampled by a study yielded greater evidence for senescence (also shown by Fricke et al, 2023;Vrtilek et al, 2022), studies tended to sample a low proportion of maximum adult lifespan (median = ~25%, Supplementary Fig. 10).…”
Section: Aim 1: Effects Of Advancing Male Age On Ejaculate Traitssupporting
confidence: 67%
“…sperm number, concentration, and ejaculate size. This increase could be associated with their mating status, as most studies (>75%) on insects in our meta-analysis kept males as virgin (see Fricke et al, 2023;Richardson and Zuk 2022, who show similar results in males and females, respectively). Low mating rates could result in old insects accumulating more sperm and producing larger ejaculates than young males, because many insects have continuous spermatogenesis throughout their lives Hiroyoshi et al, 2021;Malawey et al, 2019;Reinhardt et al, 2011).…”
Section: Biological Moderatorsmentioning
confidence: 79%
See 3 more Smart Citations